Use of hemoglobin as alternative to peroxidases in cholesterol amperometric biosensors - Souza, Tâmera T.L.; Moraes, Marli L. [UNESP]; Ferreira, Marystela (Elsevier, 2013)
Sophisticated molecular architectures can be produced with the layer-by-layer (LbL) method, which may combine distinct materials on the same film. In this study, we take advantage of this capability to produce cholesterol amperometric biosensors from LbL films containing hemoglobin (Hb) and cholesterol oxidase in addition to the polyelectrolytes poly(allylamine hydrochloride) (PAH) and poly(ethylene imine) (PEI). Following an optimization procedure, we found that an LbL film deposited onto ITO substrates, with the architecture ITO(PEI/Hb)5(PEI/COx)10, yielded a sensitivity of 93.4 μA μmol L-1 cm-2 for cholesterol incorporated into phospholipid liposomes, comparable to state-of-the-art biosensors. Hb acted as efficient electron mediator and did not suffer interference from phospholipids. Significantly, cholesterol could also be detected in real samples from chicken egg yolk, with no effects from potential interferents, including phospholipids. Taken together these results demonstrate the possible fabrication of low cost, easy-to-use cholesterol amperometric biosensors, whose sensitivity can be enhanced by further optimizing the molecular architectures of the LbL films. © 2012 Elsevier B.V.
Keywords: Amperometric measurements; Biosensor; Cholesterol; Enzymes; Hemoglobin; LbL film; Amperometric biosensors; Chicken egg yolk; Cholesterol oxidase; Electron mediator; Interferents; Layer-by-layer methods; Low costs; Molecular architecture; Optimization procedures; Phospholipid liposomes; Poly(allylamine hydrochloride); Polyethyleneimine; Real samples; Architecture; Liposomes; Optimization; Phospholipids; Biosensors